Gas reserves calculation based on the results of reservoir pressure distribution modeling - Zakharchuk, Oksana (Technology audit and production reserves, 2022)
The object of this study is the gas-bearing layer B-26 of the Zakhidne-Radchenkivsʹke gas condensate field (Ukraine). A bottleneck in the process of exploration and experimental and industrial operation of the Zakhidne-Radchenkivsʹke gas condensate field was the ambiguous data on extractive reserves (values that were calculated by different authors range from 14 thousand to 424 million m3). At present, the field is mothballed, which is why the use of a new approach to calculating the initial gas reserves could be useful for deciding to start developing a single productive layer B-26. During the study, such theoretical research methods were used as the system analysis of the information used, numerical modeling based on the combined finite-element-difference method, the methods of visual representation of the information received, as well as analytical methods. The method of calculating gas reserves proposed in this work combines a volumetric method and the simulation of filtration processes using a combined finite-element-difference method. The latter makes it possible to take into consideration the structure of the reservoir, which is heterogeneous in terms of permeability, and to adequately, at the quantitative level, to describe the distribution of non-stationary reservoir pressure around the extractive well. By applying an analytical formula based on the values of average reservoir and downhole pressures, the radii of the well's feed circuit at different stages of the reservoir development have been calculated. Thus, the active area (and volume) of the reservoir can be determined, according to which the extractive reserves of the deposit are calculated. The mining reserves of the Zakhidne-Radchenkivsʹke field, estimated in this way, amount to 174 million m3 of gas. The method for calculating reserves proposed in this study could prove useful for deciding on the further development of the Zakhidne-Radchenkivsʹke gas condensate field. Combining the volumetric method with the results of modeling filtration processes is an operational method for calculating the reserves of the reservoir, opened by one mining well. In this case, the application of the combined finite-element-difference method makes it possible to take into consideration the complex heterogeneous structure of the reservoir and predict the distribution of reservoir nonstationary pressures around the extractive well. The current study that used the Zakhidne-Radchenkivsʹke gas condensate field in Ukraine as an example is interesting when calculating the reserves of layers of complex structure all over the world, whereby the productive reservoir is opened by a single mining well.